EFFORTS TO IMPROVE SCIENCE PROCESS SKILLS THROUGH GUIDED DISCOVERY LEARNING MODEL IN CLASS V SDN KEJI, WEST UNGARAN SEMARANG - Azizah Azizah; Rhino Ayu Primandani (Universitas Tadulako, 2020)
The background of this research study is low yields fifth grade science students Keji Elementary School District of West Ungaran Semarang District. The formulation of the problem is whether to use guided discovery learning model can improve the science process skills Elementary School fifth grade students Keji District of West Ungaran Semaran district. The purpose of this research is to improve science process skills through guided discovery learning model in the Elementary School fifth grade students Keji District of West Ungaran Semarang District. This type of research is classroom action research using a model Kemmis and Mc Taggart. Data collection techniques in this research is observation. Data analysis using quantitative data analysis to process the observation of science process skills of students and qualitative analysis for data processing skills of teachers. From the research that has been obtained, it can be seen that learning science by using guided discovery learning model can improve the skills of fifth grade science students Keji Elementary School District of West Ungaran Semarang District on the material light and nature. This was shown by an increase in the acquisition value of science process skills of students in learning science after applying the learning model guided discovery.